2019
DOI: 10.9734/ajfar/2019/v4i130047
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fish Farming in Plateau State, North Central Nigeria

Abstract: World leaders are making concerted effort to tackle the menace of food insecurity brought about by upsurge in human population, climate change and displacement of farming communities due to civil unrest in some part of the world. This study was undertaken to assess the current status of fish farming in Plateau State and suggest possible ways of ameliorating any observed challenges for increased fish production. The study evaluated the challenges affecting fish farming in the study area. Structured interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The reason could be that concrete and mobile tank farmers need complete feed supplies which contains all the nutrients require for optimal growth and therefore more money was spent on feeds. This result is in line with Adewumi (1994) and agrees with Igoche et al (2019) who reported that the cost of feeds consumed more than half of the total cost of production in catfish farming. This is followed by cost of fingerlings (22.16 and 29.63%) for the two systems.…”
Section: Average Revenue Variable Cost Gross Aquaculture Production S...supporting
confidence: 92%
See 1 more Smart Citation
“…The reason could be that concrete and mobile tank farmers need complete feed supplies which contains all the nutrients require for optimal growth and therefore more money was spent on feeds. This result is in line with Adewumi (1994) and agrees with Igoche et al (2019) who reported that the cost of feeds consumed more than half of the total cost of production in catfish farming. This is followed by cost of fingerlings (22.16 and 29.63%) for the two systems.…”
Section: Average Revenue Variable Cost Gross Aquaculture Production S...supporting
confidence: 92%
“…Years of experience and educational level were significant at 5% level, implying that years of experience and educational level had positive relationship with output. Fish farmers with longer years of experience would be early adopters of innovation and will be willing to pass on innovation to intending farmers (Igoche et al, 2019). Educational level had positive coefficient and relationship with output, implying that farmers with good education can be more creative, innovative and imbibe good record keeping in farm business.…”
Section: Mobile Tank Systemmentioning
confidence: 99%